Oxygen Generation by Carbon Dioxide Glow Discharge and Separation by Permeation Through Ultrathin Silver Membranes. Issue 4 (5th April 2019) - Premathilake, Dilshan; Outlaw, Ronald A.; Quinlan, Ronald A.; Byvik, Charles E.
Abstract: A six Torr CO2 glow discharge in combination with a heated W mesh‐reinforced ultrathin Ag membrane is used to generate molecular oxygen. The Ag membrane is a commercially available 25‐μm‐thick Ag foil backed by a 25‐μm‐thick W electroformed mesh. The permeation flux is inversely dependent on the membrane thickness and exponentially dependent on the membrane temperature. Calculations show that a pressure differential of 1 atmosphere can be supported by the W mesh/Ag foil membrane at temperatures up to 350 °C. In this work, a glow discharge for pressures between 2 and 15 Torr CO2 and temperatures up to 500 °C were reported. The DC glow discharge was produced initially with a solid Ag rod cathode, 2 mm in diameter, and then with a 7‐mm‐diameter Ag rod machined into a hollow cathode, located 5 mm from, and normal to, the Ag membrane anode. The voltage was varied from 440 to 620 VDC with currents up to 41 mA. A stable flux of 1.61 × 10 15  O2  molecules·cm −2 ·s −1 is observed for a membrane temperature of 450 °C and a CO2 pressure of 6 Torr. With ~4‐m 2 surface area, this approach is competitive with the present mission qualified Mars Oxygen In‐Situ Resource Utilization Experiment (MOXIE) system planned by National Aeronautics and Space Administration (NASA) for the 2020 Mars rover mission which generates ≈12 g/hr O2 . The proof of concept technique presented herein can be substantially improved by further reduction of the membrane thickness, refinement of the cathode, and glow discharge plasma. Key Points: A silver membrane is used to separate oxygen created from a carbon dioxide glow discharge This method can be used to generate oxygen from the Martian atmosphere Proof of concept experiments validates method of generating pure oxygen from carbon dioxide